2015
DOI: 10.1021/acs.cgd.5b01559
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabricating Hierarchically Porous Metal–Organic Frameworks via a Template-Free Strategy

Abstract: Tunable Cu-BTC mesoporous metal–organic frameworks (mesoMOFs) are prepared conveniently through a template-free strategy under solvothermal conditions. Nanosized microporous Cu-BTC particles pack to form mesopores with sizes that can be controlled (26–72 nm) by simply varying the synthesis temperature. This template-free and controllable strategy can be applied using other organic solvents to obtain mesoMOF materials that possess similar tunable mesopores. Furthermore, the as-synthesized hierarchically porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 50 publications
(73 reference statements)
4
38
0
Order By: Relevance
“…The introduction of a secondary pore system in order to create a hierarchical porous structure has been proven as an advantageous strategy in zeolite catalysis [163]. Recently, this approach was developed for modifying nanoporous MOF matrices [164][165][166][167][168]. This way of the rational design of MOF porous structures extends essentially application fields in catalysis by MOF materials.…”
Section: Play With Physical Properties: Texture Geometry and Morphologymentioning
confidence: 99%
“…The introduction of a secondary pore system in order to create a hierarchical porous structure has been proven as an advantageous strategy in zeolite catalysis [163]. Recently, this approach was developed for modifying nanoporous MOF matrices [164][165][166][167][168]. This way of the rational design of MOF porous structures extends essentially application fields in catalysis by MOF materials.…”
Section: Play With Physical Properties: Texture Geometry and Morphologymentioning
confidence: 99%
“…2d-f, these Cu-BTC_An samples also exhibit similar shapes and pore structures, with dense, uniform nanoakes randomly stacked together and abundant voids in between. Cao et al 49 and Hirai et al 50 also reported that hierarchical porous structures in MOFs are formed through the aggregation or packing of microporous nanoparticles. Although void structures are clearly observed in all of the Cu-BTC_An samples (Fig.…”
mentioning
confidence: 99%
“…Mn(II), have received increasing attention, owing to its high spin ground state can be obtained from strong exchange interactions between 3d electrons [1][2][3][4][5][6][7][8][9][10]. Noted that, the development of coordination chemistry, many research efforts have been devoted to novel ways to fabricate, characterize and explore fundamental magnetic phenomena [11][12][13][14][15][16][17][18][19][20][21][22][23]. Coordination polymers (CPs) with polynuclear units based on Co(II) and Mn(II) have fascinating architectures and physical properties with widespread applications, such as catalysis, sorption, magnetism and electrical conductivity [24][25][26][27][28][29][30].…”
Section: Magnetic Materials Based On Transition Metal Ions With Polynmentioning
confidence: 99%